2017
DOI: 10.14687/jhs.v14i4.4778
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical perceptions of school administrators concerning school and ideal school<p>Okul yöneticilerinin okul ve ideal okula ilişkin metaforik algıları

Abstract: Metaphor used in a variety fields of social sciences can be defined as the meaning transfer from one object to other which have similarities in terms of some aspects. It can also be defined as making relations between abstract things with concrete everyday things to be understood them easily. When addressed in terms of education administration, it has been observed that metaphors are often used while designing curriculums, planning activities, making motivations for learning and creative thinking trainings. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…There are number of researches in several disciplines at both national and international levels involving usage of metaphors in education (Grady, Fisher and Fraser, 1996;Nikitina and Furuoka, 2008;Saban, 2009;Strugielska, 2008;Thomas and Beauchamp, 2010;İbret and Aydınözü, 2011;Güner, 2012;Tortop, 2013;Özkan and Taşkın, 2014;Baş and Gezegin, 2015;Hamilton, 2016;Güçlü and Duran, 2017;Doğan, 2017;;Beyoğlu and Ergin, 2018;Storlie, Giegerich, Harris and Byrd, 2018;Çatak and Yıldız, 2018;Duran and Aladağ, 2018;Bauer, 2018;Değirmenci, 2019). However, it has been observed that there is only a limited number of studies which comparatively examine the perceptions of prospective teachers being educated in different departments regarding the meanings which they attribute to the concept of homeland.…”
mentioning
confidence: 99%
“…There are number of researches in several disciplines at both national and international levels involving usage of metaphors in education (Grady, Fisher and Fraser, 1996;Nikitina and Furuoka, 2008;Saban, 2009;Strugielska, 2008;Thomas and Beauchamp, 2010;İbret and Aydınözü, 2011;Güner, 2012;Tortop, 2013;Özkan and Taşkın, 2014;Baş and Gezegin, 2015;Hamilton, 2016;Güçlü and Duran, 2017;Doğan, 2017;;Beyoğlu and Ergin, 2018;Storlie, Giegerich, Harris and Byrd, 2018;Çatak and Yıldız, 2018;Duran and Aladağ, 2018;Bauer, 2018;Değirmenci, 2019). However, it has been observed that there is only a limited number of studies which comparatively examine the perceptions of prospective teachers being educated in different departments regarding the meanings which they attribute to the concept of homeland.…”
mentioning
confidence: 99%